2005
DOI: 10.1128/jvi.79.11.7024-7041.2005
|View full text |Cite
|
Sign up to set email alerts
|

5′-Terminal Deletions Occur in Coxsackievirus B3 during Replication in Murine Hearts and Cardiac Myocyte Cultures and Correlate with Encapsidation of Negative-Strand Viral RNA

Abstract: Adult human enteroviral heart disease is often associated with the detection of enteroviral RNA in cardiac muscle tissue in the absence of infectious virus. Passage of coxsackievirus B3 (CVB3) in adult murine cardiomyocytes produced CVB3 that was noncytolytic in HeLa cells. Detectable but noncytopathic CVB3 was also isolated from hearts of mice inoculated with CVB3. Sequence analysis revealed five classes of CVB3 genomes with 5 termini containing 7, 12, 17, 30, and 49 nucleotide deletions. Structural changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
251
3
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(285 citation statements)
references
References 120 publications
25
251
3
3
Order By: Relevance
“…In the case of CB3V, terminal deletions arise more rapidly in either intact heart tissues or primary myocardial cell cultures than in other cells, suggesting that the cellular environment has a strong influence (Kim et al, 2005). However, one virus associated with persistent virus infections appears to have evolved a specific strategy for truncating its termini.…”
Section: Evidence For a Specific Mechanism For Terminal Truncationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of CB3V, terminal deletions arise more rapidly in either intact heart tissues or primary myocardial cell cultures than in other cells, suggesting that the cellular environment has a strong influence (Kim et al, 2005). However, one virus associated with persistent virus infections appears to have evolved a specific strategy for truncating its termini.…”
Section: Evidence For a Specific Mechanism For Terminal Truncationmentioning
confidence: 99%
“…CB3V genomes can be detected in tissue from previously infected individuals, yet infectious viruses have been almost impossible to isolate, suggesting that CB3V may be capable of viral persistence. Evidence for a persistence mechanism came from sequence analysis, which showed that CB3V genomes within infected tissues possessed 59-terminal deletions of between 7 and 49 nt (Kim et al, 2005). It was found that there was a correlation between the presence of complete or truncated termini, and acute versus persistent infection, respectively (Kim et al, 2005).…”
Section: Examples Of Associations Between Terminal Truncations and Pementioning
confidence: 99%
See 1 more Smart Citation
“…Human enteroviruses cause acute myocarditis and are etiologically linked as causes of dilated cardiomyopathy, a disease that can proceed to heart failure (2,3,11,20,22). Enteroviral RNA persistence in adult hearts with myocarditis or dilated cardiomyopathy in the absence of detectable infectious virus has been a common observation (reviewed in references 3, 11, and 12) but remained without adequate explanation until we demonstrated that, during replication in isolated murine cardiomyocytes and in hearts of infected mice, CVB3 can naturally delete sequence information at the genomic 5Ј terminus (13). This work showed that, weeks following the inoculation of mice with CVB3, mouse myocardium in which no cytolytic virus was evident was able to transmit virus to cell cultures, which, in turn, showed no cytopathic effects (CPE) despite the detection of CVB3 RNA.…”
mentioning
confidence: 99%
“…In addition, purified CVB3TD virions encapsidate both positive-and negative-strand RNA in a strand ratio similar to that of total RNA from CVB3TD-infected cell cultures. Because CPE in CVB3TD-infected cell cultures are not measurable, a method was developed to titer infectious CVB3TD using real-time quantitative reverse transcription-PCR (RT-PCR) analysis of the viral RNA content in CVB3TD preparations (13). It was not surprising to note deviations from wild-type enteroviral replication, as the region in the 5Ј NTR that is progressively deleted (the cloverleaf RNA structure termed domain I) is also an essential region for viral replication (1,17,19).…”
mentioning
confidence: 99%